2019
DOI: 10.1039/c9ra08352a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-doped carbon dots and application in vanillin detection based on collisional quenching

Abstract: N-doped carbon dots (NCDs) exhibit bright blue emissions and have been used as viable fluorescent probes in the turn-off fluorometric assay for vanillin detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The decrease process revealed that ClO − may selectively oxidate the amino N groups on the surface of N, F-CDs to form new substances with less π – π and n – π conjugate systems at 300–600 nm, thereby leading to the fluorescence quenching of N, F-CDs. These results proved that a dynamic quenching mode occurred between N, F-CDs and ClO − [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 73%
“…The decrease process revealed that ClO − may selectively oxidate the amino N groups on the surface of N, F-CDs to form new substances with less π – π and n – π conjugate systems at 300–600 nm, thereby leading to the fluorescence quenching of N, F-CDs. These results proved that a dynamic quenching mode occurred between N, F-CDs and ClO − [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 73%
“…[46] Generally, the type of quenching mechanism can be indirectly predicted by the quenching constant from the standard Stern-Volmer equation, i. e.,F 0 =F ¼ 1þ k q t 0 Fe 3þ ½ �¼ 1 þ K sv ½Fe 3þ �, where [Fe 3 + ] is the concentration of the quencher, k q is the bimolecular quenching constant, τ 0 is the fluorescence lifetime of PEG2000-CPDs without addition of Fe 3 + and K sv is the quenching constant. [52,53] As shown in Figure 11, the Stern-Volmer plot exhibits a good linear relationship and the K sv is calculated as 1.65×10 3 M À 1 . Based on the obtained τ 0 (3.40 ns) and K sv (1.65×10 3 M À 1 ), as well as the equation k q t 0 ¼K sv , the k q is calculated to be 4.85×10 11 L mol À 1 s À 1 , which is much higher than the maximum collision quenching constant (1.0-2.0)×10 10 L mol À 1 s À 1 .…”
Section: Quenching Mechanismmentioning
confidence: 81%
“…Based on the obtained τ 0 (3.40 ns) and K sv (1.65×10 3 M À 1 ), as well as the equation k q t 0 ¼K sv , the k q is calculated to be 4.85×10 11 L mol À 1 s À 1 , which is much higher than the maximum collision quenching constant (1.0-2.0)×10 10 L mol À 1 s À 1 . [53] Thus, the fluorescence quenching of PEG2000-CPDs by Fe 3 + should follow a static quenching mechanism. Simultaneously, the Fe 3 + can provide empty orbits for the unshared electrons of the oxygenated and nitrogenous functional groups on the surface of the CPDs to form the non-luminous complexes.…”
Section: Quenching Mechanismmentioning
confidence: 99%
“…Content of vanillin cannot exceed 70 mg kg −1 ; this makes it particularly important to test their content. Wang et al [138] used glucose and tyrosine as raw materials, without using any strong acid and oxidant, only by a simple hydrothermal method to synthesize the N-g-CDs; its selective detection found that most metal ions can quench fluorescence, especially Fe 3+ , in order to prevent its inter ference, the masking agent EDTA was added. In the presence of EDTA, the metal ions did not interfere with N-g-CDs, and similar structures of molecules such as salicylic acid, indenyltriol, p-bromophenol, and p-nitrotoluene were studied, only vanillin effectively quenched the fluorescence, therefore vanillin could be selectively detected Table 2 summarises the application in food in the last three years.…”
Section: Applications For Analysis and Detection In Foodmentioning
confidence: 99%